2013
DOI: 10.1080/00221325.2012.670672
|View full text |Cite
|
Sign up to set email alerts
|

Situational, Interpersonal, and Intrapersonal Characteristic Associations With Adolescent Conflict Forgiveness

Abstract: ABSTRACT. Given the voluntary nature of adolescent friendships, forgiveness of interpersonal transgressions has been identified as a critical aspect of maintaining these relationships. However, transgression forgiveness is related to a range of situational (e.g., transgression severity), interpersonal (e.g., friendship commitment), and intrapersonal (e.g., victim's empathy) factors. Data from 161 adolescents were used to examine the nature of the relationships between these factors and forgiveness and to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Also in Berry et al study (2005), forgivingness (measured with The Trait Forgiveness Scale) was negatively correlated with trait anger. Furthermore, adolescent reports of forgiveness were negatively related to their anger resulting from their friend's hypothetical transgression (Johnson, Wernli, & Lavoie, 2013 No other styles of anger expression (assertion, support seeking, rumination, diffusion, and avoidance) were linked to forgiveness. In reference to depression, forgiveness of self for a specific transgression was found to be connected with a lower level of depressive affect (Wohl, DeShea, & Wahkinney, 2008).…”
Section: Positive-negative Affectivity and Emotional Control And Formentioning
confidence: 87%
See 1 more Smart Citation
“…Also in Berry et al study (2005), forgivingness (measured with The Trait Forgiveness Scale) was negatively correlated with trait anger. Furthermore, adolescent reports of forgiveness were negatively related to their anger resulting from their friend's hypothetical transgression (Johnson, Wernli, & Lavoie, 2013 No other styles of anger expression (assertion, support seeking, rumination, diffusion, and avoidance) were linked to forgiveness. In reference to depression, forgiveness of self for a specific transgression was found to be connected with a lower level of depressive affect (Wohl, DeShea, & Wahkinney, 2008).…”
Section: Positive-negative Affectivity and Emotional Control And Formentioning
confidence: 87%
“…They have included intrapersonal characteristics, interpersonal determinants, and situational factors (Johnson, Wernli, & Lavoie, 2013). However, forgiveness scholars have suffered from the lack of empirical integration (Fehr, Gelfand, & Nag, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…If an adolescent is unable to live up to these expectations, or other behaviors that might reasonably be expected of a friend, such as helping a friend in need rather than avoiding or blaming the friend , then the friendship will suffer MacEvoy and Asher 2012). Given that these transgressions are likely to occur, however, understanding and forgiveness are other important skills for successful friendships (Johnson et al 2013).…”
Section: Friendship As a Marker Of Social Competence Distinct From Pementioning
confidence: 99%
“…Social skills implicated in friendship stability include being able to navigate conflict and friendship transgressions without resorting to dissolution, for instance by using social perspective-taking skills and being forgiving (Johnson et al 2013;Selman 1980). Another skill implicated in the quest to maintain friendships is the ability to ''suspend egoism'' and act as equal partners in the friendship (Hartup 1996;Sullivan 1953).…”
Section: Friendship Quality and Friendship Stability As Markers Of Somentioning
confidence: 99%
“… Hui and Chau (2009) found that empathizing with the offender and thinking from the perspective of others is a key strategy in the process of forgiveness. Adolescents with higher levels of empathy report more frequent forgiveness in the face of relationship aggression than those with lower levels of empathy ( Johnson et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%